2015
DOI: 10.4103/0972-0707.157256
|View full text |Cite
|
Sign up to set email alerts
|

The effect of multiple autoclave cycles on the surface of rotary nickel-titanium endodontic files: An in vitro atomic force microscopy investigation

Abstract: Aims:To observe and study the effect of multiple autoclave sterilization cycles, on the surface of nickel-titanium (NiTi) files.Materials and Methods:The file used for this study was the Mtwo file (VDW) and ProTaper (Dentsply). The apical 5 mm of the files were attached to a silicon wafer and subjected to autoclave cycles under standardized conditions. They were scanned with an AFM after 1, 5, and 10 cycles. The unsterilized files were used as control, before start of the study. Three vertical topographic para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Whether our findings may be clinically relevant in vivo depends on the number of times of the files' reuse, disinfection control protocol, such as immersing files in 6% NaOCl for 5 min before use, 27 and autoclave sterilization which cumulatively prolongs file contact with NaOCl. 20 , 28 Therefore, multiple uses of these endodontic files may increase the risk of instrument breakage.…”
Section: Discussionmentioning
confidence: 99%
“…Whether our findings may be clinically relevant in vivo depends on the number of times of the files' reuse, disinfection control protocol, such as immersing files in 6% NaOCl for 5 min before use, 27 and autoclave sterilization which cumulatively prolongs file contact with NaOCl. 20 , 28 Therefore, multiple uses of these endodontic files may increase the risk of instrument breakage.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Although the NiTi rotary instruments have excellent surface smoothness and cyclic fatigue resistance, 32 the stresses caused by mechanical instrumentation increase the SR, force of friction, and likelihood of instrument failure. 33 Therefore, understanding the effects of mechanical stresses on SR of NiTi rotary instruments may suggest useful information in terms of surface defects and clinical safety. 24 …”
Section: Discussionmentioning
confidence: 99%
“…By increasing the SR, friction between instrument and tooth increases, hence compromising the cutting efficiency, cyclic fatigue strength, and safety. 32 33 Therefore, such surface defects may potentially lead to the formation of stress concentration areas, crack propagation, and fracture during the clinical use. 44 45 The machining grooves and pits that are potential areas for stress concentration can be reduced by electropolishing of rotary file surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Based on SEM analysis, Razavianet et al reported an increase in roughness directly related to the number of sterilizations performed [ 64 ], while Nair et al showed that, following sterilization, there is an increase in the surface roughness of the instruments due to an increase in the surface irregularities of the metal alloy, which could represent the cores from which the crack starts and the fracture of the tool occurs under cyclical fatigue [ 65 ].…”
Section: Discussionmentioning
confidence: 99%